From the patient's point of view: medical ethics and the moral imagination. Issue 4 (December 1991) - Elliott, C; Elliott, B
Abstract : This paper concerns the difficulties of imagining the subjective point of view of another human being, and the relevance of these difficulties to medical decisions. It explores especially the difficulties of imagining the experience of the mentally impaired, and examines several standards for decision-making: the 'prior expressed wishes standard', the 'substituted judgement standard', and the 'best interests standard'.